2010
DOI: 10.1111/j.1574-6941.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resource quantity and resource stoichiometry on microbial carbon-use-efficiency

Abstract: The carbon-use-efficiency (CUE) of microorganisms is an important parameter in determining ecosystem-level carbon (C) cycling; however, little is known about how variance in resources affects microbial CUE. To elucidate how resource quantity and resource stoichiometry affect microbial CUE, we cultured four microorganisms - two fungi (Aspergillus nidulans and Trichoderma harzianum) and two bacteria (Pectobacterium carotovorum and Verrucomicrobium spinosum) - under 12 unique C, nitrogen (N) and phosphorus (P) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(206 citation statements)
references
References 30 publications
10
194
0
2
Order By: Relevance
“…It is likely that the species composition of the microbial biomass would differ in 0_0 from the other treatments due to the change in CNP stoichiometry. Since fungal biomass contains relatively more C than bacterial biomass, it is suggested that fungi might have a higher C-demand than bacteria, while bacteria are more constrained by nutrient ratios (Keiblinger et al 2010). We found only a weak correlation between the CFE and SIR measurements of C mic , and variation was particularly large in the high P-fertiliser treatments (15_15, 30_0, 30_30).…”
Section: Microbial Community Structurementioning
confidence: 56%
“…It is likely that the species composition of the microbial biomass would differ in 0_0 from the other treatments due to the change in CNP stoichiometry. Since fungal biomass contains relatively more C than bacterial biomass, it is suggested that fungi might have a higher C-demand than bacteria, while bacteria are more constrained by nutrient ratios (Keiblinger et al 2010). We found only a weak correlation between the CFE and SIR measurements of C mic , and variation was particularly large in the high P-fertiliser treatments (15_15, 30_0, 30_30).…”
Section: Microbial Community Structurementioning
confidence: 56%
“…For example, Bolat (2014) and found thinning increased labile organic carbon, but decreases have been reported in other studies (Schilling et al, 1999;Hassett and Zak, 2005). In addition, because seasonal variations in soil temperature and aboveground vegetation might affect the ability or strategy of microbial decomposers to efficiently use SOC, the thinning effect on labile SOC and enzymatic activities may vary seasonally (Balser and Wixon, 2009;Liptzin and Silver, 2009;Keiblinger et al, 2010;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Plant biomass data at the site also suggest that because of the lack of moisture, NPP (net primary production) was decreased relative to controls . The potential reduction in labile carbon and nitrogen entering the rhizosphere could also be a partial cause for the decline of microbial phyla such as Verrucomicrobia who are known to be heterotrophs (Hedlund et al, 1997) and are sensitive to nitrogen ratios (Keiblinger et al, 2010). An analysis of the effect of warming on community structure showed no significant difference despite the effect on abundance.…”
Section: Effects Of Warming Under Droughtmentioning
confidence: 99%